USTU as the core of innovative territorial cluster «oil and gas technologies» - V. E. Kuleshov; O. V. Yurchenko (Высшее образование в России)
The article is devoted to an actual modern problem of integration of two major spheres of the state and public life – science and business – on the basis of educational institution of the higher professional technical education institution. Ukhta State Technical University is has become a platform to create for creation of the innovation and educational cluster, – which can be regarded as a real product of such integration. In the article we reveals the possible types of similar clusters and a form of their strategies and formulates the conceptual bases of for the creation of innovation and educational cluster on the basis of USTU are defined here.